Pelatihan E-Learning berbasis Simulasi PheT Bagi Guru MIPA di MA Darul Ulum Palangka Raya - Yuliani, Hadma; Qamariah, Zaitun; Rohmatika, Ria (Lembaga Einstein College, 2024)
Based on the observations result in MA Darul Ulum Palangka Raya, the teachers are facing problems in creating fun learning for the students. Besides, the teachers are rarely integrating learning with technology. Therefore, the community service team provides a solution in form of e-learning Workshop by using PhET Simulation for MIPA teachers in MA Darul Ulum Palangka Raya. The purpose of the Workshop is to prepare MIPA teachers to be able to use and integrate PhET Simulation media in MIPA learning. This activity had been attended by eleven (11) teachers. The final result of this community service is the development of e-learning media based on PhET Simulation in MIPA learning. This media is expected to be an option to increase the students’ interest in MIPA learning.